Strengthening Leadership Succession Through The Delegation Of Authority Strategy Model In Corporate Succession Planning In Jakarta - Yuni Pratikno; Harries Madiistriyatno; Meirna Milisani; Haspul Naser; Eric Hermawan (UNIVED Press, 2025)
Determine how delegation of authority can help employees develop managerial skills. Research objectives: First, we examine the benefits of delegation of authority for leadership skill development; second, we examine the effectiveness of succession planning in preparing future leaders; and third, we investigate the role of delegation in facilitating organizational transitions integrated with succession planning. Methodology: SEM with Smart PLS 4.0. The sample consisted of 92 respondents, selected using the non-probability sampling method. Results: An effective succession-planning strategy involves delegating authority to stimulate talent development and facilitate the placement of qualified workers in significant positions. Conclusions and suggestions: HR professionals can use this matrix to put succession planning concepts into practice, especially where delegation of authority is involved, by integrating the nine-box matrix methodology. In addition, HiPo Mapping will assist in the recruitment, training and placement of skilled workers in key positions within the organisation.